2006
DOI: 10.1179/016164106x97982
|View full text |Cite
|
Sign up to set email alerts
|

Dobesilate inhibits the activation of signal transducer and activator of transcription 3, and the expression of cyclin D1 and bcl-XL in glioma cells

Abstract: Treatment with inhibitors of FGF down-regulates the STAT3 signaling pathway. These alterations could be correlated to the already observed inhibition of cell proliferation and promotion of apoptosis in glioma cell cultures by dobesilate. The reported results may open new avenues for developing new treatments against these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…The death receptor and mitochondrial death pathways may be linked by Bcl-XL, which subsequently activates the proteolytic activation of effector caspases-3 to trigger the mitochondrial dysfunction and cytochrome c release [17][18][19]. Also, DEX pre-treatment has been recently reported to interfere with apoptotic death in brain tumour cells by the transcriptional activation of a Bcl-XL gene [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The death receptor and mitochondrial death pathways may be linked by Bcl-XL, which subsequently activates the proteolytic activation of effector caspases-3 to trigger the mitochondrial dysfunction and cytochrome c release [17][18][19]. Also, DEX pre-treatment has been recently reported to interfere with apoptotic death in brain tumour cells by the transcriptional activation of a Bcl-XL gene [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Gu et al used higher concentration (50 vs. 15 nM) of the decoys, more prolonged (24 vs. 4 h) lipofectamine-mediated transfection, and a different control decoy (scrambled vs. mutated), which could also contribute to the differences in the results. Cuevas et al [2006b] reported that dobesilate-a synthetic FGF inhibitor-reduces the level of Stat3 phosphorylation in C6 glioma cells, with a concurrent reduction in expression of Bcl2l1 and Ccnd1 assessed by immunocytochemistry. These results appear contradictory to our results suggesting that Stat1, and not Stat3, maintains the expression of Bcl2l1 in the C6 glioma cells.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment of C6 glioma cells with dobesilate in vitro triggered apoptosis and growth arrest (80). Further studies in glioma cells showed that dobesilate significantly inhibited constitutive expression of tyrosine phosphorylated STAT-3 (81), activation of the MAPK extracellular signal-regulated protein kinases 1/2 (82), and expression of the prosurvival proteins Bcl-xL and cyclin D1 (81). These results support the idea that dobesilate increased apoptosis and decreased cell growth and survival in part by blocking STAT-3 activation.…”
Section: Inhibition Of Upstream Kinasesmentioning
confidence: 99%